Association of AhRR rs2292596 with male infertility in 422 Vietnamese individuals - Huu Dinh, Tran; Xuan Canh, Nguyen; Huong Thao, Dinh; Lan Anh, Luong Thi; Minh Duc, Bui; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2021)
Male infertility is a reproductive disease in men caused by multiple factors ranging from harmful lifestyle habits to endogenous genetic elements. This study aimed to investigate the association between the polymorphism AhRR rs2292596 and male infertility. Total DNA was extracted from blood of 422 Vietnamese samples including 218 non-obstructive azoospermic and oligozoospermic patients and 204 healthy controls. The genotypes of the polymorphism were determined by PCR-RFLP method. The distribution of genotypes and their relationship with male infertility were analyzed by statistical methods. The results indicated that rs2292596 AhRR followed Hardy-Weinberg equilibrium (p-value > 0.05). However, there was association between the rs2292596 polymorphism and male infertility in the three models (additive, dominant, and recessive) (p-value > 0.05). The investigation would help enrich the knowledge about the influences of genetic factors on male infertility in the Vietnamese population.